Developments in litigation economics - Gaughan, Patrick A.; Thornton, Robert J. (Emerald, 2005)
This book is a collection of original articles on recent developments in the rapidly growing field of litigation economics, also called forensic economics. The book spans the more popular areas of litigation economics including: personal-injury economic loss analysis, commercial damages analysis securities litigation, punitive damages, employment litigation and intellectual property litigation. The authors of the articles are respected leaders in their fields. This series: includes titles covering a wide range of topics within the fields of economics and finance. It is international in scope, and serves as an invaluable reference for those interested in these fields.
Keywords: Business finance.; Business enterprises -- Finance.; elektronické knihy; electronic books